2013
DOI: 10.9790/5736-0334553
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of photocatalytically active ZnO nanoparticle by surface capping with poly vinyl pyrrolidone.

Abstract: Nanoparticles of zinc oxide (ZnO) were prepared by the precipitation method from zinc sulphate (ZnSO 4 .7H 2 O) and sodium bicarbonate (NaHCO 3). Organization, stabilization of the ZnO nanoparticles from further growth and partially inhibiting the photodegradation was achieved by capping with poly vinyl pyrrolidone (PVP). Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to investigate the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…The absorption peak at 1373.6 cm −1 is due to the С–Н bond in PVP [21]. Other important peaks at 1287.6 cm −1 and the doublet at 1437.8 cm −1 , 1422.4 cm −1 are assigned to the C–N stretching vibrations and the attachment of CH 2 groups in the pyrrole ring of PVP [2223]. A comparison of the spectra of the prepared ZnO/PVP nanoparticles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption peak at 1373.6 cm −1 is due to the С–Н bond in PVP [21]. Other important peaks at 1287.6 cm −1 and the doublet at 1437.8 cm −1 , 1422.4 cm −1 are assigned to the C–N stretching vibrations and the attachment of CH 2 groups in the pyrrole ring of PVP [2223]. A comparison of the spectra of the prepared ZnO/PVP nanoparticles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are various reports of the synthesis of ZnO nanomaterials by using various capping agents and surfactants like polyethylene glycol (PEG), ethylenediaminetetraacetic acid (EDTA), polyvinylpyrrolidone (PVP), triethanolamine (TEA), tetraethylammonium bromide (TEAB), 2-aminothiol, 3-aminopropyl trimethoxysilane, tetraethyl orthosilicate (TEOS), mercaptosuccinic acid, 3-mercaptopropyl trimethoxysilane, oleic acid, aminopropyltriethoxysilane, etc. [20][21][22][23][24][25][26][27][28]. Sudha et al [21] showed that PEG capped ZnO NPs prevents agglomeration and with increasing PEG concentration, various morphologies and sizes of ZnO NPs can be obtained.…”
Section: Introductionmentioning
confidence: 97%
“…It has been demonstrated that ZnO NPs when capped with 2-aminothiol, EDTA, TEA and TEAB can improve the optoelectronic properties, and particles with various shapes and morphologies have been synthesized with those capping agents [22][23]. In addition to capping agents, use of surfactants during synthesis of ZnO can also change the optical and electronic properties of ZnO NPs [24][25][26][27][28]. R. Hong et al [24] showed the reduction of photocatalytic activities and decrease in agglomeration of the particles using oleic acid as the coating.…”
Section: Introductionmentioning
confidence: 98%
“…A peak at 1643.27 cm -1 was assigned to the stretching vibration of the C=O. Other imperative peaks at 1287.50 cm -1 and the doublet at 1438.03, 1422.04 cm -1 were assigned to the C-N stretching vibrations and the attachment of CH 2 groups in the pyrrole ring of PVP [42,43]. The spectra of optimized GLB thin film (Figure 3c) exhibited all the principle peaks present in the PVP thin film.…”
Section: Ftir Analysismentioning
confidence: 99%